The study of the fertilizing effect of wheat straw ash in a greenhouse experiment - Kremper, Rita; Hidvégi, Réka; Balláné Kovács, Andrea; Loch, Jakab (Acta Agraria Debreceniensis, 2016)
The effect of wheat straw ash as a fertlizizer was studied in a pot experiment with an acidic sandy loam soil (pHKCl=4.9) with weak K and P supply. The test plant was ryegrass (Lolium perenne). The treatments were the following: 1. control untreated soil, 2. NPK fertilizer, 3. small dose of ash (1.4 g kg-1), 4 large dose of ash (2.8 g kg-1), 5. small dose ash completed with NP fertilizers. Soil parameters (pHH2O, pHKCl, ammoinum-lactate soluble P, K, 0.01 M CaCl2 soluble PO43–P, K, Mn, Cu, Zn ) and plant parameters (yield, P, K, Ca, Mg, Zn, Mn uptake) were investigated. Based on the analysis of the straw ash sample and the results of pot experiment it can be stated that the wheat straw ash is suitable for the fertilization of the studied soil. The small dose ash completed with NP resulted in the largest yield increment (43%). In order of the treatments the pHKCl changes to: 4.9, 4.8, 5.2, 5.8, 5.1. As the N : P2O5 : K2O ratio is 0 : 1: 3.5 in the wheat straw ash sample, to reach optimal yield ash should be completed with N and P.